Indonesia’s macroeconomic conditions during United States-China trade war - Sulistiyowati, Liliek Nur; Pratama, Sandhika Vistaylen (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
The trade war between the United States and China can affect the Indonesian economy. It is because the United States and China are Indonesia's main trading partners in International trading. Indonesia's macroeconomic indicators affected by the trade war are exports, imports, interest rates, and inflation. This research examines the trade war's partial and simultaneous effect on Indonesia's macroeconomic conditions, such as exports, imports, interest rates, and inflation. The data used in this study is secondary data from the Central Bureau of Statistics (BPS) and Bank Indonesia (BI) in 2017 – 2020. The data analysis technique used is MANOVA (Multivariate Analysis of Variance). The empirical results showed that trade war simultaneously affects exports, imports, interest rates, and inflation. Meanwhile, the trade war partially affects exports, imports, and interest rates but not inflation. Our research concluded that trade conflicts between Indonesia's two main trading partners, namely the United States and China, affect Indonesia's macroeconomic conditions, especially on exports, imports, interest rates, and inflation. Indonesia must take strategic steps to anticipate the impact of the trade war, especially on export, import, and interest rate policies.